Letter from J.F. Grossklaus to James Curtis Booth, September 17, 1853 - Grossklaus, J.F. (1853)
Requests information concerning James Curtis Booth's (1810-1888) courses.
Keywords: Booth, James Curtis, 1810-1888; Lectures and lecturing; Chemistry teachers